Extended Reality Applications in Cardiac Surgery and Interventional Cardiology - Vitaliy F. Petrov; Mariana V. Pankiv (Ukrainian Journal of Cardiovascular Surgery, 2023)
Extended reality combines the real and digital worlds. This technology has found applications in all fields of medicine, including cardiac surgery and interventional cardiology. The paper describes the application of three types of extended reality, namely virtual, augmented and mixed realities.The aim. To explain the principles of operation of various types of extended reality using non-medical and medical applications as examples; to analyze the data from specialized publications in the field of cardiac interventions.Materials. Articles from the Pubmed database.Results. The article highlights important details of the heart and blood vessels image creation technique with which users operate. Primary data is obtained from imaging modalities like tomography or ultrasound, then it is segmented and processed for the virtual viewing. In virtual reality, three-dimensional (3D) images of the heart defects are analyzed in depth, and virtual manipulations can be performed that simulate the course of the operation. Virtual reality includes printing the heart on a 3D printer with subsequent executions on physical models, both diagnostic dissections and therapeutic surgical or endovascular simulations. In augmented reality, the created image of the internal anatomy of the defect is present near the surgeon, without interfering medical manipulations. In mixed reality, a virtual image is superimposed on the patient’s body, creating a detailed navigation map.Conclusions. Extended reality application deepens the understanding of anatomy due to stereoscopic visualization of the structure of the heart and blood vessels. Creating a model of a patient’s heart defect and simulating an operation on it shortens the “learning curve”, improves the professional skills of surgeons and cardiologists, and also allows for surgical and endovascular interventions individualization. Planning interventions in cardiac surgery and interventional cardiology with extended reality technologies influences decision-making and reduces the duration of operations.